ANALISIS PENGARUH FRAUD TRIANGLE TERHADAP FRAUDULENT FINANCIAL REPORTING DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Dini Rahayu (Prosiding Seminar Nasional Pakar, 2020)
The purpose of this study is to examine the effect of fraud in theory fraud triangle to indication fraudulent financial statistics with audit quality as moderating variable on companies listed on the Indonesia Stock Exchange . The  population  in  this  study  consists  of  all companies  listed on the Indonesia Stock Exchange 2016-2018 period. Data collected with method purposive sampling, obtained as many as 57 companies that became sample research. Data used is secondary data in the form of annual report the company that made sample research. Data analysis was performed by logistic regression analysis, with a significance value of 5%. The results of the study concluded that razionalization has a negative effect on indication fraudulent financial reporting. Meanwhile, financial stability ,effective supervision and rationalization did not significantly influence indication fraudulent financial reporting